Optimalisasi Keuntungan Penjualan Tahu Dengan Metode Grafik Program Linier Berbasis QM For Windows - Utari, Yanik; Sutejo, Heru; Irjanto, Nourman S (Innovative: Journal Of Social Science Research, 2025)
Tofu is typically produced in small to medium-scale industries, with the production technology still being very basic, heavily reliant on manual labor, and lacking optimization. Efforts to optimize tofu sales profits require strategies that focus on maximizing sales revenues. This study aims to optimize the profits from tofu production conducted in the morning and evening by employing linear programming through the graphical method. Data collection on operational costs, raw materials, and production quantities, developed into a mathematical model, can be utilized to achieve efficient and accurate decision-making. The Linear Programming Graphical Method can be used to identify the optimal point for maximizing profits. The research successfully demonstrated that by applying the Linear Programming Graphical Method, Mas Aziz Tofu Factory could significantly increase its sales profits from tofu production in the morning and evening. This study supports the business owner of Mas Aziz Tofu Factory in optimizing production and formulating strategies to maximize profits in the future.